Additional diagnostic value of first-pass myocardial perfusion imaging without stress when combined with 64-row detector coronary CT angiography in patients with coronary artery disease. Issue 13 (24th April 2014) - Osawa, Kazuhiro; Miyoshi, Toru; Koyama, Yasushi; Hashimoto, Katsushi; Sato, Shuhei; Nakamura, Kazufumi; Nishii, Nobuhiro; Kohno, Kunihisa; Morita, Hiroshi; Kanazawa, Susumu; Ito, Hiroshi
Abstract : Objective: Multi-detector coronary CT angiography (CCTA) can detect coronary stenosis, but it has a limited ability to evaluate myocardial perfusion. We evaluated the usefulness of first-pass CT-myocardial perfusion imaging (MPI) in combination with CCTA for diagnosing coronary artery disease (CAD). Methods: A total of 145 patients with suspected CAD were enrolled. We used 64-row multi-detector CT (Definition Flash, Siemens). The same coronary CCTA data were used for first-pass CT-MPI without drug loading. Images were reconstructed by examining the signal densities at diastole as colour maps. Diagnostic accuracy was assessed by comparison with invasive coronary angiography. Results: First-pass CT-MPI in combination with CCTA significantly improved diagnostic performance compared with CCTA alone. With per-vessel analysis, the sensitivity, specificity, positive predictive value and negative predictive value increased from 81% to 85%, 87% to 94%, 63% to 79% and 95% to 96%, respectively. The area under the receiver operating characteristic curve for detecting CAD also increased from 0.84 to 0.89 (p=0.02). First-pass CT-MPI was particularly useful for assessing segments that could not be directly evaluated due to severe calcification and motion artefacts. Conclusions: First-pass CT-MPI has an additional diagnostic value for detecting coronary stenosis, in particular in patients with severe calcification.